إشكالية الجندر والهوية: رواية ظل هيرمافروديتوس لبدرية البدري - هرندي, كريمة (جامعة الوادي - university of Eloued, 2022)
إنّ رواية ظل هيرمافروديتوس للروائية بدرية البدر محاولة منها لمعالجة مسألة وإشكالية الجندر والهوية، من خلال تطرقها إلى العديد من المداخل الهوياتية، مركزة في ذلك على إشكاليات فرعية لها علاقة بالإشكالية الأساسية منها إشكالية الصراع الجيلي، إشكالية الحرية والتحرر، إشكالية التقبل الاجتماعي في سياق اجتماعي معين، حاولت عن طريقه الروائية تحديد المعالم الأساسية لوجود هذه الظاهرة بذات المجتمع العربي. The shadow of Hermaphroditus novel by Badriya Al-Badr is an attempt to address the issue and the problem of gender and identity, by addressing many of the identity entries, focusing on sub-problems related to the basic problem, including the problem of the generational conflict, the problem of freedom and liberation, the problem of social acceptance in a particular social context, through which the novelist tried to determine the basic features of the existence of this phenomenon in the same Arab society.
مقال
Keywords: هوية؛ جندر؛ امرأة؛صورة؛رجل; Identity; gender; Woman; image; man